Uji Kualitatif Dan Penetapan Kadar Flavonoid Total Ekstrak Etanol Herba Pegagan (Centella asiatica) Dengan Variasi Konsentrasi Pelarut - Wahyu Yuliana Solikah; Annisa Fatmawati; Adhi Gunawan; Astri Yeni Defri (Journal of Pharmaceutical and Sciences, 2023)
Gotu Kola (Centella asiatica) has been known as a medicinal plant that has pharmacological activity in various diseases. One of the many bioactive compounds found is flavonoids. This study aims to determine the effect of concentration on total levels of flavonoids in the ethanol extract of Centella asiatica herb (EEHP). The method of measuring total flavonoid content was UV-Visible spectrophotometry with a maximum lambda of 412 nm and using quercetin as a reference standard. The results of total flavonoid levels in EEHP 50%, EEHP 70%, EEHP 80%, and EEHP 96% were 5.58 mgQE/g; 5.24 mgQE/g; 6.67 mgQE/g; 11.92 mgQE/g. The ANNOVA test showed a significant difference in the results of 96% EEHP flavonoid levels with a sig value of 0.001 (<0.5). Trigger concentration is proven to affect the levels of flavonoids contained in the extract. The highest levels of flavonoids were obtained at 96% EEHP, which is 11.92 mgQE/g.